A potentiated cooperation of carbonic anhydrase IX and histone deacetylase inhibitors against cancer. (1st January 2020) - Ruzzolini, Jessica; Laurenzana, Anna; Andreucci, Elena; Peppicelli, Silvia; Bianchini, Francesca; Carta, Fabrizio; Supuran, Claudiu T.; Romanelli, Maria Novella; Nediani, Chiara; Calorini, Lido
Abstract: The emergence of tumour recurrence and resistance limits the survival rate for most tumour-bearing patients. Only, combination therapies targeting pathways involved in the induction and in the maintenance of cancer growth and progression might potentially result in an enhanced therapeutic efficacy. Herein, we provided a prospective combination treatment that includes suberoylanilide hydroxamic acid (SAHA), a well-known inhibitor of histone deacetylases (HDACs), and SLC-0111, a novel inhibitor of carbonic anhydrase (CA) IX. We proved that HDAC inhibition with SAHA in combination with SLC-0111 affects cell viability and colony forming capability to greater extent than either treatment alone of breast, colorectal and melanoma cancer cells. At the molecular level, this therapeutic regimen resulted in a synergistically increase of histone H4 and p53 acetylation in all tested cell lines. Overall, our findings showed that SAHA and SLC-0111 can be regarded as very attractive combination providing a potential therapeutic strategy against different cancer models.